Arthroplasty in hand surgery FESSH instructional course book 2020 - Schindele, Stephan F.; Giddins, Grey; Bellemère, Philippe (Thieme, 2021)
"Recent research suggests the lifetime risk of hand arthritis may be greater than 40%. Concurrently, advances in small joint arthroplasty have greatly improved the treatment and outcomes in patients following trauma or suffering from arthritis, joint stiffness, and instability of joints in the hand and wrist. Arthroplasty in Hand Surgery: FESSH Instructional Course Book 2020 provides in-depth coverage of the surgical reconstruction or replacement of these joints. Edited by renowned hand surgeons Stephan Schindele, Grey Giddins, and Philippe Bellemère, this unique resource features contributions from an international who's who of experts. Organized in five sections and 35 chapters, the generously illustrated book encompasses the full spectrum of modern arthroplasty techniques. In section one, the anatomy, biomechanics, and mode of action of the finger and thumb joints are discussed. It concludes with an intriguing history of hand arthroplasty. Sections two to four cover the latest arthroplasty procedures to treat impaired joints of the fingers (including proximal interphalangeal and distal interphalangeal), thumb, and wrist, respectively. The last section discusses arthroplasty of the distal radioulnar joint. This highly practical resource is essential reading for surgeons in training and practicing orthopaedic surgeons and hand specialists"--